Flexible Leading Spaces: An Exploration of Leader Experiences of Shared Office Spaces - Bissett, Rebekah (Auckland University of Technology, 2020)
Despite widespread research into the topic of Flexible Learning Environments (FLE) in schools as well as government policies supporting a shift to FLE schools, the way that schools choose to provide workspaces for educational leadership has not had the same level of attention. Deans working as part of a middle leadership team may experience a range of workspace configurations, ranging from open-plan shared workspaces which might reflect the principles of FLE schools, to more traditional single-cell office spaces. Schools in the process of designing or redesigning their workspaces for educational leadership teams would benefit from a greater understanding of how shared workspaces are experienced by those working in them. The overarching aim of this study was to critically examine the lived experiences of Deans working in shared office spaces in a New Zealand secondary school context Considering the shift towards FLEs in the New Zealand education context, this study aimed to discover the extent to which schools are adopting shared workspaces for educational leadership teams. Following on from this, the study aimed to investigate the ways in which the configuration of a workspace influences educational leadership teams’ experiences of their roles, and to investigate the ways in which leadership spaces affect leadership practice. This study employed a qualitative approach that was positioned within an ontological and epistemological stance that knowledge derived from human experiences is both valid and important in developing understanding in research. Semi-structured interviews were conducted with seven middle leaders working in shared Deans’ workspaces across three different schools across Auckland. Findings were collated into tables by interview question and analysed using a thematic analysis approach. These results were then presented by theme to answer the three research questions which guided this study. • In what ways are schools adopting shared workspaces for educational leadership teams? • How does the configuration of workspaces for educational leadership teams influence their experiences of their roles? • In what ways do leadership spaces affect leadership practice? The data revealed that flexible leadership spaces foster leadership learning, collaborative and visible leadership approaches and can exist within fixed architectural design. The physical configuration of space was found to influence the leadership practices and experiences of Deans and could be considered a tool for supporting collegial and collaborative practice. The space does not dictate a method of leadership practice in and of itself. The benefits of increased connection, collegiality and collaborative practice as enabled through the shared space was found to be useful in mitigating disconnection and isolation experienced by middle leaders disconnected from their departments and had benefits for the wellbeing of the Deans working in the shared space over and above any stressors which were associated with the space. These stressors were all linked to tensions between transparency, privacy and confidentiality. Successfully implemented shared workspaces for educational leadership teams can therefore provide a supportive environment which fosters leadership growth as well as enhancing wellbeing for educational leaders.
Keywords: Deans; Flexible learning spaces; Middle leadership; Secondary schools; Educational leadership; Shared workspaces; Collaborative leadership